Private Sector Actions to Enable Climate-Smart Agriculture in Small-Scale Farming in Tanzania - Quail, Sheryl; Onyango, Leah; Recha, John W.M.; Kinyangi, James (Springer, 2016)
The private sector plays the most important role in financing agricultural investments, innovation and information dissemination where constraints on government investment render private sector actions more important. In East Africa, little is known about the participation of small businesses, independent traders, farmer organizations, large-scale wholesalers, marketing boards and cooperatives in climate-smart agriculture (CSA) and their potential role in its diffusion to small-scale farmers. In particular, the informal sector is out of view even though it forms the backbone of rural agrarian economies. This study examines relationships between private sector actors and farmers and examines supply chains of agricultural inputs, as well as agricultural product value chains. The potential for using the Quality Declared Seed (QDS) system to disseminate CSA bean and potato varieties is assessed, as is the commercial maize seed supply chain and its impact on agrobiodiversity. Finally, farmer trust of private sector actors, traders in particular, is evaluated. The data used is from a survey of 100 farmers and semi-structured interviews with traders, local input suppliers, transporters and marketing organizations.